Face Management and Issues of Power, Solidarity, and Distance: Socio-Pragmatic Influences on Literary Discourses - V. Vinod Kumar; Vijay Singh Thakur; Justin James (Universitas Sanata Dharma, 2019)
Literature, in many ways, reflects human societies. Literature is mainly a linguistic and aesthetic reflection of how human beings conduct their personal and social lives. The use of language by nature is a social activity. Human beings conduct all aspects of their lives through language. In the backdrop of this premise, human communication is, by nature, social communication. Furthermore, language is shaped by societies and, in turn, societies are also shaped by the language they shape. The human communication functions and works on the social aspects related to who speaks to whom, when, in what language, where, how, and for what purpose. In all contexts, the sociolinguistic aspects of power principle, solidarity principle, distance, and face management play an influential role in determining the tenor, tone and mode of communication. This paper attempts to examine, analyze and discuss the socio-pragmatic perspectives that shape, guide, and give direction to inter-personal human communication. This analytical discussion of the socio-pragmatic aspects of language use will be carried out through sociolinguistic analyses of dialogic discourses from the magnum opus A Suitable Boy (ASB) authored by Vikram Seth, which is considered to be an authentic socio-cultural document of India. Keywords: face management, power principle, socio-pragmatic influences, solidarity principle